ANALYSIS MODEL OF THE EFFECT OF ASSETS, EQUITY AND DEBT ON PROFITS IN PHARMACEUTICAL SUB-SECTOR COMPANIES AT THE INDONESIA STOCK EXCHANGE FOR THE PERIOD 2014 – 2021 - Surono, Yunan; Irwanto, Telly Zuvilla (Fakultas Hukum dan Ekonomi Bisnis, 2023)
This study aims to determine and analyze the effect of variable assets, equity and debt on the profits of pharmaceutical sub-sector companies on the Indonesia Stock Exchange for the period 2014 – 2021. The independent variables of the study are assets, equity and debt as independent variables with profit as the dependent variable. Data and facts obtained from the financial statements of issuer companies have the value of assets, equity, debt and profits in the pharmaceutical sub-sector during the study period has a considerable and significant difference in value and fluctuates. This study used the Smart Partial Least Square (PLS) 3.0 software program. The results showed 1) Asset variables have no effect on profit variables in pharmaceutical sub-sector companies on the Indonesia Stock Exchange for the period 2014 - 2021. 2) The equity variable has no effect on the profit variable. 3) Variable debt has no effect on variable profit.